Self-determinable Development of Small Islands - Ishihara, Masahide; Hoshino, Eiichi; Fujita, Yoko.; SpringerLink (Online service) (Singapore : Springer Singapore (Imprint), 2016)
This book aims to clarify the present situation of the relations between small island countries and territories on the one hand and the great powers, mainland areas, and mega-islands on the other, and explores how small island countries and territories preserve and build their identity under globalization. This book is divided into five parts. The first part presents papers on issues that are related to Okinawa: the American military presence, the formation of a global human network, and the history of and language revitalization in Okinawa. The second part includes papers on security in East Asia and the Pacific Region: the history of and present issues in international relations within the South and East China Sea areas. The third part presents papers on economic issues and social developments on small islands. The fourth part deals with ocean policies and marine resource management in the Pacific Region by the United States, Australia, and Japan. Finally, the fifth part presents papers on the revitalization of three indigenous languages. All the chapters of the book are based on the achievements of the research project "Towards New Island Studies: The Ryukyus as an academic node between East Asia and Oceania" conducted by the International Institute for Okinawan Studies at the University of the Ryukyus. This 5-year project was funded by the Japanese Ministry of Education, Culture, Sports, Science and Technology and aimed to contribute academically to the creation of sustainable and self-determinable societies in small island regions. This work will be extremely useful and informative for readers in small island countries and territories and for researchers who are interested in small island issues to understand the current situation and who wish to consider effectual and feasible solutions.
Part I: Okinawan Agenda -- 1 The Okinawa U.S. Military Base Issue and Human Security -- 2 Formation and Development of an Okinawan Global Network Using an Island Hub -- 3 Ryukyu Kingdom Diplomacy with Japan and the Ming and Qing Dynasties -- 4 Language Revitalization Efforts in the Ryukyus -- Part II: International Context -- 5 Geopolitics, Self-Determination, and China's Rise in Oceania -- 6 The Similarities and Differences between Tensions over the Senkaku Islands and Dokdo Island -- 7 Taiwan's East and South China Sea Policies and the U.S. Factor -- Part III: Economic and Social Development -- 8 Small Islands Developing States and Globalization: Impacts and Development Potential -- 9 Small Island Destinations and International Tourism: Market concentration and distance vulnerabilities -- 10 Self-determination for the Communication Policy in the Pacific Islands -- Part IV: Ocean Policies -- 11 Management of Islands and their Surrounding Ocean Areas and Japan's Ocean Policy under the New Ocean Regime -- 12 The United States National Ocean Policy: Priorities, Benefits, and Limitations in the Insular Pacific -- 13 Challenges and Opportunities in Managing Remote Islands: The Australian Practice -- Part V: Indigenous Languages -- 14 Gefpago na Dinagi: Decolonization and the Chamorro Language of Guam -- 15 Ainu Languages: Correct, Good, and Less So -- 16 Welsh Language Policy: A Long Twentieth Century.
Keywords: Regional economics; Social policy; Economic policy; Development economics